FAKTOR-FAKTOR YANG MEMPENGARUHI WISATAWAN DALAM MELAKUKAN PEMESANAN AKOMODASI MELALUI ONLINE TRAVEL AGENTS DI KAWASAN WISATA UBUD - Wikanatha Sagita, Putu Agus; Kusuma Negara, I Made (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 2 (2019): Jurnal IPTA (December 2019), 2019)
This study aims to (1) Identifying the characteristics of tourists who have booked accommodation through Online Travel Agents in Ubud Tourist Area, (2) Identifying factors that encourage tourists to book accommodation through Online Travel Agents in Ubud Tourist Area , (3) Identifying what is the most dominant factor encouraging tourists to book accommodation through Online Travel Agents in Ubud Tourist Area. Data in this study was conducted with observation, interview, questionnaire and literature study techniques. Data analysis technique used is quantitative descriptive analysis and factor analysis. The characteristics of respondents in this study based on age are dominated by tourists with an age range of 21-30 years, which is 53.3% or with a total of 96 people. Based on the length of stay dominated by tourists who stay 1-4 days, which is 57.8% or with a total of 104 people. The Online Travel Agent most used by respondents is booking.com, which is 48.9% or used by 88 people. Based on the analysis of factors produced four factors that influence tourists who book accommodations through online travel agents in the Ubud Tourist Area, namely 1) Efficiency factors: (a) Saving Energy, (b) Saving Time, (c) Shopping every time. 2) Preference Factors: (a) Economical, (b) Product Use, (c) Price Competition, and (d) References. 3) Psychological Factors: (a) Learning, (b) Perception, (c) Motivation, and (d) Facilities and Infrastructure. 4) Trust Factors: (a) Trust in the Internet, (b) Trust in Applications, and (c) Security Perceptions.